Correlation and assessment of vitamin D deficiency with disease severity in patients suffering from pemphigus vulgaris - Paracha, Mohammad Majid; Khan, Abdul Qayyum; Sardar, Adan; Kashif Kamal; Arfa Ikram; Noor, Sahibzada Mahmood (Journal of the Pakistan Medical Association, 2025)
Objective: To determine correlation between vitamin D deficiency and severity of pemphigus vulgaris. Method: The prospective, cross-sectional study was conducted at the Department of Dermatology, Lady Reading Hospital, Peshawar, Pakistan, from December 2021 to June 2022, and comprised patients of pemphigus vulgaris, confirmed by histopathology and direct immunofluorescence. An expert dermatologist examined the patients at baseline to minimise inter-observer bias, and the Pemphigus Disease Area Index score was calculated for each patient. Blood samples were drawn from the medial-cubital vein, and centrifuged at 3000rpm for 10 min at 40C to check for serum vitamin D levels using the enzyme-linked immunosorbent assay technique. Data was analysed using SPSS 22. Results: Of the 89 patients, 49(55.1%) were females and 40(49.9%) were males. The overall mean age was 38.48±13.365 years. The mean vitamin D level of the patients was 17.4882±14.70505 mg/dl, with 66(74.2%) patients having vitamin D deficiency and 7(7.9%) having vitamin D insufficiency. There was negative but non-significant correlation of vitamin D level with disease severity (r =-0.131, p=0.22).. Vitamin D deficiency had no significant association with age, gender, area of living, socioeconomic status, duration of disease and educational level of the patients (p>0.05). Conclusion: Serum vitamin D level was found to have a negative correlation with severity of pemphigus vulgaris. Key Words: Pemphigus vulgaris, Vitamin D deficiency, Chronic autoimmune bullous.